The Effect of Shadowing Technique on Students' Intonation (RETAIN, 2020)
Shadowing technique is one of the listening techniques in which the listener is required to repeat word-by-word or phrase by phrase. Listening as the main activity of this technique helps the students to master listening skills. Listening deals with intonation, stress, grammatical structure, recognize speech sounds, background knowledge, etc. Many students faced difficulties in learning listening skills. They felt unfamiliar with the accent of the speakers. Furthermore, in the speed of listening, students feel the text being too fast from time to time. To solve the problem, the intonation aspect should be mastered first by the students. The aim of this study was to know the effect of the shadowing technique on students’ intonation. This study was quantitative research and the data was taken from the test. The findings of this study showed that there was a weak effect on intonation after the teacher applied the shadowing technique in listening.